2005
DOI: 10.1196/annals.1341.009
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Biology of the Transverse Tubules in Heart

Abstract: Ca(2+) sparks in heart muscle are activated on depolarization by the influx of Ca(2+) through dihydropyridine receptors in the sarcolemmal (SL) and transverse tubule (TT) membranes. The cardiac action potential is thus able to synchronize the [Ca(2+)](i) transient as Ca(2+) release is activated throughout the cell. Increases in the amount of Ca(2+) within the sarcoplasmic reticulum (SR) underlie augmented Ca(2+) release globally and an increase in the sensitivity of the ryanodine receptors (RyRs) to be trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Traditionally, PI3K activation leads to phosphorylation of Akt, thereby regulating the activity of several cellular processes including transcription, cell proliferation, glucose metabolism, apoptosis and cell migration (Katso et al, 2001;Song et al, 2005). Our studies here have shown that reduced Vcl inhibited PI3K activation in cardiac myocytes.…”
Section: Novel Role Of Vcl In Pi3k/akt Signalingsupporting
confidence: 52%
“…Traditionally, PI3K activation leads to phosphorylation of Akt, thereby regulating the activity of several cellular processes including transcription, cell proliferation, glucose metabolism, apoptosis and cell migration (Katso et al, 2001;Song et al, 2005). Our studies here have shown that reduced Vcl inhibited PI3K activation in cardiac myocytes.…”
Section: Novel Role Of Vcl In Pi3k/akt Signalingsupporting
confidence: 52%
“…1). This transverse tubular system (t-tubules, [182]) facilitates the spatial and temporal coordination of CICR during an AP, resulting in the summation of a large number of Ca 2+ sparks, whose activation is a stochastic process [31]. In contrast, atrial myocytes lack t-tubules and thus, Ca 2+ -transients initiate in the periphery of the cell and then spread centripetally [20,110,119].…”
Section: Excitation-contraction Couplingmentioning
confidence: 99%
“…RyR2 is a tetrameric SR Ca 2ϩ channel that represents the dominant Ca 2ϩ -release channel in cardiomyocytes. 119,120 Kinetics of RyR2 channel opening is complex, with the open probability state being stabilized by several factors including cytosolic Ca 2ϩ , cyclic ADP-ribose (cADPR), caffeine, and phosphorylation by several protein kinases including PKA and Ca 2ϩ /calmodulindependent protein kinase II (CaMKII). 121,122 The closed state of RyR2 is stabilized by binding of 4 subunits of the Ϸ12-kDa FK506-binding protein FKBP12.…”
Section: Pde4d-ryr2 Interactionmentioning
confidence: 99%